Intra-Amniotic Inflammation or Infection: Suspected and Confirmed Diagnosis of "Triple I" at Term - Sara Consonni; Elettra Salmoiraghi; Isadora Vaglio Tessitore; Armando Pintucci; Valentina Vitale; Patrizia Calzi; Francesca Moltrasio; Anna Locatelli (MDPI AG, 2023)
Chorioamnionitis (CA) at term of pregnancy can have an infectious and/or inflammatory origin and is associated with adverse outcomes. Triple I (intrauterine inflammation, infection, or both, TI) has been proposed to reduce the overdiagnosis of infection and neonatal overtreatment. The aim of this study is to identify clinical and histological variables that could predict adverse outcomes when TI is suspected and/or confirmed. This retrospective cohort study included 404 pregnancies (gestational age ≥ 37 weeks) that were divided into 5 all-inclusive and mutually exclusive groups. TI was defined according to the NICHD definition of 2015, and it could be confirmed (TI+) or not confirmed (TI−) via histological examination. Signs of infection/inflammation that did not conform to the definition of TI were classified as "clinical suspicion" and could be supported (CS+) or not supported (CS−) by histology. Cases of histological chorioamnionitis (HCA) without clinical manifestation represented a fifth group. Whole placental involvement (WPLI) was defined as a histological inflammation involving the maternal and fetal sides. There were 113 TI+, 30 TI−, 186 CS+, 35 CS−, and 40 isolated HCA cases. WPLI was diagnosed in 133 cases (39.2%). Composite neonatal outcome (CNO) occurred in 114 cases (28.2%) while composite maternal outcome (CMO) occurred in 192 cases (47.5%). Compared with CS+, TI+ was more predictive of CNO (p = 0.001), CMO (p < 0.001), and WPLI (p = 0.005). WPLI was related both to CNO (p < 0.001) and to CMO (p = 0.046). TI+ and WPLI showed similar sensitivity but different specificity in predicting CNO. At logistic regression, CNO was independently predicted by TI+ (OR 2.21; p = 0.001) and by WPLI (OR 2.23; p = 0.001). Compared with CS, TI is a better predictor of CNO and can be useful for the identification of newborns at risk.